2018
DOI: 10.1017/s0031182018001385
|View full text |Cite
|
Sign up to set email alerts
|

A clinical guideline onDientamoeba fragilisinfections

Abstract: Dientamoeba fragilis (D. fragilis) is an intestinal parasite frequently detected in humans with abdominal pain and diarrhoea, but it is also commonly found in asymptomatic subjects. Hence its clinical relevance is often disputed. The introduction of polymerase chain reaction (PCR) is a versatile and sensitive diagnostic technique for the detection of intestinal parasites, and in some Western world countries PCR has almost completely replaced microscopic diagnostics. PCR has however resulted in an increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 67 publications
(150 reference statements)
1
32
0
4
Order By: Relevance
“…Data on family members were not collected, since they are rarely found in patient charts. Variation in failure rates has been shown between various regimens [36], demonstrating that a substantial part of treatment failures are not reinfections.…”
Section: Discussionmentioning
confidence: 99%
“…Data on family members were not collected, since they are rarely found in patient charts. Variation in failure rates has been shown between various regimens [36], demonstrating that a substantial part of treatment failures are not reinfections.…”
Section: Discussionmentioning
confidence: 99%
“…Dientamoeba fragilis is a non-flagellated trichomonad protozoan parasite which inhabits the human intestine and is found worldwide (Barratt et al, 2011). The prevalence of D. fragilis is very heterogeneous, depending on the geographical region and the diagnostic method used (Barratt et al, 2011; van Gestel et al, 2018), with highest levels of prevalence observed in high-income countries (Stark et al, 2016). In Europe, prevalence varies from 1.6% to 83% (González-Moreno et al, 2011; Preiss et al, 1990); in Spain, from 0.4% to 24% in children (Belda Rustarazo et al, 2008) and from 2% to 9% in adults (González-Moreno et al, 2011; Fernández-Suarez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The principal diagnostic techniques used for the diagnosis of D. fragilis are light microscopy and polymerase chain reaction (PCR) amplification of DNA from stools together with subsequent sequencing. PCR has been reported to have the higher sensitivity of these two methods (van Gestel et al, 2018). However, the correlation between PCR and clinical signs and symptoms seems to be lower than for light microscopy (Stark et al, 2010a, Stark et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal pain or cramps and diarrhea are common symptoms for Dientamoeba infection [7]. Other symptoms such as nausea, vomiting, anorexia, fever and eosinophilia have been also reported [8,9].…”
Section: Introductionmentioning
confidence: 99%